Cysteinyl leukotrienes: multi-functional mediators in allergic rhinitis - Peters-Golden, M (Blackwell Publishing Ltd, 2006)
Cysteinyl leukotrienes (CysLTs) are a family of inflammatory lipid mediators synthesized from arachidonic acid by a variety of cells, including mast cells, eosinophils, basophils, and macrophages. This article reviews the data for the role of CysLTs as multi-functional mediators in allergic rhinitis (AR). We review the evidence that: (1) CysLTs are released from inflammatory cells that participate in AR, (2) receptors for CysLTs are located in nasal tissue, (3) CysLTs are increased in patients with AR and are released following allergen exposure, (4) administration of CysLTs reproduces the symptoms of AR, (5) CysLTs play roles in the maturation, as well as tissue recruitment, of inflammatory cells, and (6) a complex inter-regulation between CysLTs and a variety of other inflammatory mediators exists.